Kajian Perbandingan Karakteristik Epigenetis Populasi Tengkorak Manusia Paleometalik Gilimanuk (Bali) dan Liang Bua, Lewoleba, Melolo dan Ntodo Leseh (Nusa Tenggara Timur) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRAC The epigenetic characteristics of Paleometallic human skull' populations from prehistoric sites of Nusa Tenggara Timur i.e. Liang Bua (Flores), Lewoleba (Lembata), Melolo (Sumba) and Ntodo Leseh (Komodo), and Gilimanuk (Bali) were studied. The aims of the study were to find wether there significant differences and biological contiguity among the populations. The subjects consisted of adult skulls from prehistoric sites of Gilimanuk (Bali), and Liang Bua, Lewoleba, Melolo and Ntodo Leseh (Nusa Tenggara Timur) from a period of transition of Late Neolithic to the beginning of Metallic Age that had an antiquity of 1500-4000 years. The subjects were selected from 20 skulls that consisted of 13 males and 7 females from Gilimanuk (Bali), and 20 skulls from Nusa Tenggara Timur consisted of 2 males and 3 females from Liang Bua, 4 males and 2 females from Lewoleba, 5 males and 2 females from Melolo, and 1 male and 1 female from Ntodo Leseh. Nonparametric statistical analysis i.e. Mann Whitney U test and Kruskal-Wallis, were used to compare the means of independent groups. Informative, discriminative, and determinative quality existed in various kinds of variables were used to make balance factors which reduced variable's representativeness. Independent variables consisted of age